Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of the Iberian Peninsula - Shavrin, Alexey V.; Zanetti, Adriano (Zootaxa, 2021)
New taxonomic, diagnostic, and faunistic data for twelve species of the genus Lesteva Latreille, 1797 of the Iberian Peninsula and adjacent territories are provided. Six species are (re-) described and illustrated: L. (s.str.) aterrima Lohse, 1967, L. (s.str.) balearica Lohse, 1967, L. (s.str.) lusitana Lohse, 1955, L. (s.str.) mariei Jarrige, 1963, L. (s.str.) mateui Jarrige, 1954, and L. (s.str.) osellai Zanetti & Shavrin, sp.n. (Portugal, Spain). The following new synonymies are established: L. (s.str.) fontinalis Kiesenwetter, 1850 = L. (s.str.) fontinalis gustavi Herman, 2001 syn.n., L. (s.str.) mateui = L. cazorlana Lohse, 1987 syn.n., L. (s.str.) pubescens Mannerheim, 1830 = L. fageli Lohse, 1960 syn.n. A lectotype is designated for L. (s.str.) fontinalis. Images of habitus and aedeagi of L. (s.str.) aterrima, L. (s.str.) balearica, L. (s.str.) cazorlana, L. (s.str.) fontinalis, L. (s.str.) hanseni Lohse, 1953, L. (s.str.) mariei Jarrige, 1963, and L. (s.str.) pubescens are provided. A key to the species of Portugal and Spain, and a distributional map for some species are provided. New records are reported for L. (Lestevina) sicula heeri Fauvel, 1871 from Morocco, L. (s.str.) hanseni Lohse, 1953 and L. (s.str.) pubescens from Portugal, and L. (s.str.) mariei from Spain.